The Effect of Agility Ladder Drill on The Speed and Agility of Arema Academy Students U-10 to U-13 Years Old - Ahmad Hafidh Taqiyuddin; Arief Darmawan (STKIP Paasundan Press, 2025)
This study aims to evaluate the impact of agility ladder drill training on improving the agility and speed of Arema Academy students aged U-10 to U-13. Soccer requires high agility and speed, especially in young players. This study used an experimental method with a One Group Pretest-Posttest design. The sample consisted of 20 players selected through purposive sampling. The training was conducted over 16 sessions, three times per week. Speed was measured using a 30-meter run test, and agility was assessed using the Illinois Agility Test. Data analysis employed the Shapiro-Wilk normality test and the Paired Sample T-Test. The normality test results indicated that the data were normally distributed (p > 0.05). The results of the Paired Sample T-Test showed a significant increase in agility (mean difference = 1.76283; p = 0.000) and speed (mean difference = 0.60790; p = 0.000) after training. These findings are consistent with previous studies indicating that agility ladder drills improve directional change ability, reaction speed, and body coordination. Therefore, agility ladder drills are recommended in early-age soccer training programs to optimize physical performance